(untitled) (Research, Society and Development, 2021)
Tuberculosis caused by Mycobacterium bovis is an important disease in cattle e a great problem for animal health that can reach humans. For the diagnosis of the infection and the consequent sanitary measures, the National Program for Control and Eradication of Brucellosis and Tuberculosis (PNCEBT) establish the use of intradermal tuberculin tests. The aim of this study was to analyze the response to the avian and bovine tuberculin (PPD) developed by cattle sensitized with inactivated inoculum of M. avium and M. bovis. Another aim was to compare the results of the caudal fold test (CFT), the comparative cervical test (CCT), and the simple cervical test (SCT) for tuberculosis diagnosis in the sensitize animals and in animals that have not been sensitized. Repetition of the tests did not influence the proportion of positive results. There were animals sensitized with M. bovis showing reaction up to more than 500 days post sensitization. In animals sensitized with M. avium, the specificity of the CCT was higher than that of CFT and SCT, and CCT was able to discriminate the unspecific reaction induced by M. avium inoculum. In animals sensitized with M. bovis, CCT had lower sensitivity than the other two tests. The SCT and CCT cut-off with the best combination of sensitivity and specificity was lower than that adopted by the PNCEBT for the tuberculosis diagnosis in naturally infected animals. SCT hat good agreement with the other two tests, but the agreement between CFT and CCT was only moderate. The frequency of the responses to tuberculin did not show Gaussian distribution, but in some post sensitization periods or after square root or logarithmic transformation of the data.